(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Arundhati Roy won the Booker prize of 1997 for the stylistic innovations in her debut novel. An examination of Roy’s narrative style is very complicated, for its structure infers numerous dimensions of perusing. She writes in a style especially unique in relation to huge numbers of her contemporaries. To express her musings Roy invents a nearly code-language suffused with cross-references, so it appears the novel invents the language in which it is composed. The man centric, sex and standing biased, politically sensitized and manipulated society is constructed employing cinematic procedures. The epic arrangements with cruelty that spills out of built up organizations of society like family and marriage, apparatus for keeping law and enforcing equity, and the complicated framework deciding sex imbalance in the public arena. The foul play that the untouchables need to suffer, the affront and abuses ladies in the public arena need to tolerate and the trials and tribulations, the unprotected need to experience under brutalized apparatus in a standing ridden and progressive society, these become the topic of Arundhati Roy’s book.